Annotated Catalog of Iranian Aradidae (Hemiptera: Heteroptera: Pentatomomorpha: Aradoidea) - Ghahari, Hassan; Heiss, Ernst (Zootaxa, 2012)
In addition to previous contributions to a general catalog of Iranian Heteroptera, this paper presents a catalog of the flat bug family Aradidae. Nine species and subspecies belonging to two genera (Aneurus Curtis and Aradus Fabricius) of two subfamilies (Aneurinae and Aradinae) are reported.